Automated parking lot management for Bengali license plates using hough transformation and image segmentation - Mahmud, Abul Ahsan; Dores, Bishal Peter; Nahid Ul Islam (BRAC University, 2014)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2014.